Composite diaphragm and lithium ion secondary battery

By providing a trapezoidal cross-sectional wet bonding polymer coating on the base film surface of the lithium-ion secondary battery separator, the problem of insufficient wet bonding performance between the separator and the positive and negative electrode in the prior art is solved, and higher bonding performance and electrochemical safety are achieved, which is suitable for industrial production.

CN222813859UActive Publication Date: 2025-04-29SHENZHEN SENIOR TECH MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202421493195.3
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2025-04-29
Estimated Expiration
2034-06-27

AI Technical Summary

Technical Problem

The prior art has complex operation and limited effects in improving the wet bonding performance of the lithium-ion secondary battery separator and the positive and negative electrode.

Method used

By providing the first coating and the second coating in the base film surface and part of the holes thereof, and defining at least one is a wet bond polymer coating, and the cross-sectional shapes of the two are respectively a regular trapezoid and an inverted trapezoid, respectively, to improve the bonding performance.

Benefits of technology

It realizes excellent wet bonding performance between the composite diaphragm and the positive and negative electrodes, reduces the probability of electrolyte leakage, improves electrochemical safety performance, and is suitable for industrial production applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222813859U_ABST
    Figure CN222813859U_ABST
Patent Text Reader

Abstract

The utility model provides a composite diaphragm and lithium ion secondary battery, the composite diaphragm comprises a base membrane, at least one surface of the base membrane and part of holes are provided with at least one first coating, at least one second coating and at least one blank area, the first coating and / or the second coating are / is limited to be a wet adhesive polymer coating, and the first coating and / or the second coating are / is a wet adhesive polymer coating. The first coatings and the second coatings are alternately distributed in the width direction of the base film, at least one blank area is arranged between the first coatings and the second coatings, the cross section of each first coating is in a regular trapezoid shape, the cross section of each second coating is in an inverted trapezoid shape, the width of the base film ranges from 0.2 m to 8 m, and the width of the base film ranges from 0.2 m to 8 m. The first coating and the second coating can be mutually limited in space and can be tightly attached along respective bevel edges after being pressed, so that the wet-state bonding performance of the composite diaphragm and positive and negative pole pieces is greatly improved, meanwhile, an existing slurry formula does not need to be changed, and the composite diaphragm is more suitable for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of diaphragms, and in particular relates to a composite diaphragm and a lithium ion secondary battery. Background Art

[0002] The diaphragm is a key component in lithium-ion secondary batteries. It is sandwiched between the positive and negative electrodes of the lithium-ion secondary battery. Its main function is to prevent the positive and negative electrodes from directly contacting each other and causing short circuits, and to allow ions in the electrolyte to pass through. Therefore, the diaphragm is required to have good adhesion to both the positive and negative electrodes.

[0003] At present, in order to improve the wet bonding performance between the diaphragm and the positive and negative electrodes, the improvement methods of the diaphragm can be roughly divided into the following two types: one is to design and modify the chain segments of the polymer, that is, to improve the wet bonding performance of the polymer by adjusting the polymerization monomers during the polymerization process; the other is to mix multiple polymers and improve the wet bonding performance by adjusting the formula of the polymer slurry system.

[0004] However, the operations of the above two improvement methods are very complicated, and the improvement of the wet bonding performance of the diaphragm is very limited.

[0005] Therefore, in view of the above-mentioned deficiencies in the prior art, it is of great significance to develop a composite separator having excellent wet bonding properties with both the positive and negative electrodes. Utility Model Content

[0006] In view of the deficiencies in the prior art, the purpose of the present utility model is to provide a composite diaphragm and a lithium-ion secondary battery, by arranging a first coating and a second coating on the surface of a base film and in some pores thereof, and limiting at least one of the two to be a wet-bonded polymer coating, and the cross-sectional shapes of the two are respectively a positive trapezoid and an inverted trapezoid and are alternately distributed, so that the obtained composite diaphragm has excellent wet bonding properties with both the positive and negative electrodes, and there is no need to adjust the slurry formula, which is more suitable for industrial production applications.

[0007] In order to achieve the purpose of this utility model, the utility model adopts the following technical solutions:

[0008] In a first aspect, the utility model provides a composite diaphragm, the composite diaphragm comprising a base membrane, at least one surface of the base membrane and part of its pores are provided with at least one (for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100 or a range consisting of any two of them) first coating, at least one (for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100 or a range consisting of any two of them) first coating, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100 or a range consisting of any two thereof) second coating layers and at least 1 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100 or a range consisting of any two thereof) blank area;

[0009] The first coating and / or the second coating is a wet-bonded polymer coating;

[0010] Along the width direction of the base film, the first coating layer and the second coating layer are alternately distributed, at least one of the blank areas is arranged between the first coating layer and the second coating layer, and the cross-sectional shapes of all the first coating layers are regular trapezoids, and the cross-sectional shapes of all the second coating layers are inverted trapezoids;

[0011] The width of the base film is 0.2 to 8 m (for example, 0.2 m, 0.4 m, 0.5 m, 1 m, 2 m, 3 m, 4 m, 5 m, 6 m, 7 m, 8 m or a range consisting of any two of them).

[0012] The composite diaphragm provided by the utility model is provided with at least one first coating, at least one second coating and at least one blank area on at least one surface of the base film and in some of its holes. Firstly, the first coating and / or the second coating are defined as wet-bonded polymer coatings. Secondly, along the width direction of the base film, the first coating and the second coating are alternately distributed, and the cross-sectional shapes of all the first coatings are regular trapezoids, and the cross-sectional shapes of all the second coatings are inverted trapezoids. The first coating with a regular trapezoidal cross-sectional shape and the second coating with an inverted trapezoidal cross-sectional shape are matched, and the two are alternately distributed on the surface of the base film, so that the two restrict each other in space, avoiding the risk of displacement or falling off due to insufficient wet bonding of the first coating or the second coating. Such a setting can also make the two coatings adhere to each other after application. After pressing, the respective oblique edges are tightly fitted, which further improves the wet bonding strength between the obtained composite diaphragm and the positive and negative electrode sheets; finally, by setting at least one of the blank areas between the first coating and the second coating, the electrolyte can be injected and can more quickly infiltrate the coating from the thickness direction of the coating, which can more effectively reduce the probability of electrolyte leakage, improve the wet bonding effect, and be more conducive to improving the electrochemical safety performance of the battery. Further, combined with the setting of the trapezoidal cross-section of the coating, after the electrolyte is injected, the electrolyte can flow more smoothly from the inclined blank area into the bottom of the polymer coating, thereby achieving infiltration of the polymer coating and further improving the electrochemical performance. In addition, the composite diaphragm provided by the utility model does not require adjustment of the existing polymer slurry formula and the existing coating process parameters, and is therefore more suitable for industrial production applications.

[0013] In the present invention, the “at least one surface of the base film” refers to at least one of the two surfaces of the base film that have the largest area and are disposed opposite to each other.

[0014] In the present utility model, the “wet adhesive polymer coating” refers to a coating containing a wet adhesive polymer, and the “wet adhesive polymer” refers to a polymer having good adhesive properties after being infiltrated with an electrolyte.

[0015] In the present utility model, the "width direction of the base film" refers to the direction on the film surface that is perpendicular to the length direction of the base film, and the "length direction of the base film" is defined as the machine transportation direction, winding direction of the base film in the production process, or the winding direction of the battery preparation process; and in the present utility model, all width directions (including the width direction of the first coating, the width direction of the second coating, and the width direction of the blank area, etc.) are defined as directions parallel to the width direction of the base film, and all length directions (including the length direction of the first coating, the length direction of the second coating, and the length direction of the blank area, etc.) are defined as directions parallel to the length direction of the base film.

[0016] In the present invention, the "trapezoide" refers to a quadrilateral with only one set of parallel opposite sides, and the side of the set of parallel opposite sides that is in contact with the base film is the lower side, and the other parallel side that is relatively far away from the base film is the upper side. Furthermore, the "regular trapezoid" refers to a trapezoid whose upper side width is smaller than that of the lower side, and the "inverted trapezoid" refers to a trapezoid whose upper side width is larger than that of the lower side. In the present invention, there is no requirement for the specific lengths of the upper and lower sides of the "regular trapezoid" and "inverted trapezoid", as long as the above definitions of "regular trapezoid" and "inverted trapezoid" are met.

[0017] In the present invention, there is no special limitation on the preparation method of the provided composite diaphragm, and it can be prepared by conventional methods in the art. For example, a first coating slurry and a second coating slurry can be prepared first, and then the two can be coated on the surface of the base film.

[0018] In the present utility model, there is no special restriction on the material type of the first coating and the material type of the second coating, as long as at least one of the first coating and the second coating is a wet bonding polymer coating. However, in order to ensure that the obtained composite diaphragm can have both excellent dry bonding properties and wet bonding properties (under electrolyte infiltration state), in a preferred embodiment, the first coating is defined as a dry bonding polymer coating, and the second coating is defined as a wet bonding polymer coating; in another preferred embodiment, the first coating is defined as a wet bonding polymer coating, and the second coating is defined as a dry bonding polymer coating.

[0019] Accordingly, in the present invention, the "dry bonding polymer coating" refers to a coating containing a dry bonding polymer, and the "dry bonding polymer" refers to a polymer having good bonding properties in a solid state (solvent-free state).

[0020] Furthermore, in the present invention, the type of dry bonding polymer in the dry bonding polymer coating is not particularly limited, as long as it is a polymer that can achieve dry bonding, for example, polymethyl methacrylate, fluorine-containing polymers, etc. can be selected; in a preferred embodiment, the dry bonding polymer includes a fluorine-containing polymer, which can provide good bonding in a dry state and can be well combined with the electrolyte in a wet state (in an electrolyte infiltration state, the following similar expressions have the same meaning) to improve the ionic conductivity of the polymer coated diaphragm; as an example, the fluorine-containing polymer includes any one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-tetrafluoroethylene copolymer or polyvinylidene fluoride-trichloroethylene copolymer.

[0021] Similarly, in the present invention, there is no particular limitation on the type of wet bonding polymer in the wet bonding polymer coating, as long as it is a polymer that can achieve wet bonding; in a preferred embodiment, the wet bonding polymer includes a polymer containing a polar group, and the polymer containing the polar group can generate a strong dipole-dipole force and chemical bonding between the interface layer and the electrode after being infiltrated with the electrolyte, thereby further providing better wet bonding performance; as a further preference, the polar group includes any one of a carboxyl group, a sulfonic acid group, a sulfone group, a cyano group or an amide group; as an example, the wet bonding polymer includes any one of polyacrylonitrile, polyamide-imide, polyetherimide sulfone, and a carboxylic acid-type polyimide.

[0022] In addition, in the utility model, the first coating and the second coating may also independently include other substances commonly used in the art, as an example, they may include inorganic particles, including but not limited to aluminum oxide, boehmite, titanium dioxide, silicon dioxide, aluminum hydroxide, magnesium oxide, etc.; as an example, they may also include adhesives, and the adhesives include but are not limited to polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyvinyl alcohol, poly (meth) acrylate, carboxymethyl cellulose and other compounds; as an example, they may also include surfactants, dispersants and other auxiliary agents.

[0023] It should be noted that, although the present invention does not specifically limit the types and combinations of materials in the first coating and the second coating in the provided composite diaphragm, it can be confirmed that all materials in the first coating and the second coating are existing materials and the combinations are all existing solutions.

[0024] In a specific embodiment, along the length direction of the base film, each of the first coating layers is continuously or discontinuously distributed on the surface of the base film and in some of its pores, and each of the second coating layers is continuously or discontinuously distributed on the surface of the base film and in some of its pores; as an example, the first coating layer as a whole can be in at least one of the shapes of a porous mesh, an island, a strip, a block or a dot, and the second coating layer as a whole can be in at least one of the shapes of a porous mesh, an island, a strip, a block or a dot. In other embodiments, the first coating layer and the second coating layer can also be in other suitable shapes.

[0025] In the present invention, there is actually no specific requirement for the number of the first coating layer, the second coating layer and the blank area, as long as at least one surface of the base film is provided with at least one first coating layer, at least one second coating layer and at least one blank area; however, in order to make the wet adhesion and dry adhesion distribution of the obtained composite diaphragm more balanced, and the obtained composite diaphragm can more fully exert good adhesion in dry and wet states; preferably, it is limited to at least one surface of the base film to be provided with at least 2 first coating layers and at least 2 second coating layers; further preferably, it is limited to at least one surface of the base film to be provided with at least 3 first coating layers and at least 3 second coating layers; further preferably, it is limited to at least one surface of the base film to be provided with at least 4 first coating layers and at least 3 second coating layers, but it is not limited to the above limitations, and the number of first coating layers and second coating layers can be set as much as possible according to the width of the base film and actual conditions.

[0026] In a preferred embodiment, the number of the dry adhesive polymer coatings is limited to be greater than the number of the wet adhesive polymer coatings, thereby achieving that the dry adhesive polymer coatings and the wet adhesive polymer coatings are alternately distributed in the width direction of the base film, and at the same time, the outermost sides in the width direction of the base film are both dry adhesive polymer coatings. This arrangement is more conducive to better positioning and bonding of the electrode piece and the composite diaphragm as a whole during the battery assembly process, avoiding the problem of the composite diaphragm and the electrode piece falling off or misaligning at the edges before packaging and injection, which ultimately affects the electrochemical safety performance.

[0027] In a preferred embodiment, the total width of the wet adhesive polymer coating is limited to ≥ the total width of the dry adhesive polymer coating. Such a setting is more conducive to ensuring that under the electrolyte infiltration state, the composite diaphragm and the positive and negative electrode sheets have a sufficient and effective bonding area to provide a sufficiently high wet bonding force, thereby effectively reducing the probability of the composite diaphragm and the electrode sheets falling off and bulging in a wet state, thereby avoiding adverse effects on the electrochemical performance of the battery.

[0028] In the present utility model, the "total width of the wet adhesive polymer coating" refers to the sum of the widths of all wet adhesive polymer coatings arranged on any surface of the base film along the width direction of the base film; similarly, the "total width of the dry adhesive polymer coating" in the present utility model refers to the sum of the widths of all dry adhesive polymer coatings arranged on any surface of the base film along the width direction of the base film; when there are multiple width dimensions along a single coating in the thickness direction, it is preferred that the width dimension is the width of the side in contact with the pole piece (i.e., the side away from the base film in the thickness direction) as the width of the single coating; when there are multiple width dimensions along the length direction of a single coating, the width is measured every 5 cm, and the average value of at least 10 width measurement values ​​is taken as the width of the single coating.

[0029] In a preferred embodiment, taking the width of the base film as 100%, the width of a single wet adhesive polymer coating is 1 to 50%, for example, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two of them. Such an arrangement is more conducive to a balanced distribution of dry adhesion and wet adhesion of the polymer-coated diaphragm, and more fully exerts good adhesion. In a more preferred embodiment, the width of a single wet adhesive polymer coating is 5 to 100 mm, for example, 5 mm, 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, 100 mm or a range consisting of any two of them.

[0030] In another preferred embodiment, taking the width of the base film as 100%, the width of a single dry adhesive polymer coating is 1 to 50% of the width of the base film, for example, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two of them. Such an arrangement is more conducive to a balanced distribution of dry adhesion and wet adhesion of the polymer-coated diaphragm, and more fully exerts good adhesion. In a more preferred embodiment, the width of a single dry adhesive polymer coating is 5 to 100 mm, for example, 5 mm, 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, 100 mm or a range consisting of any two of them.

[0031] In a preferred embodiment, the thickness of a single dry adhesive polymer coating is greater than the thickness of a single wet adhesive polymer coating. This arrangement can ensure that the dry adhesive polymer is preferentially bonded to the positive and negative electrodes during the battery assembly process, which is more conducive to improving the bonding strength between the composite diaphragm and the positive and negative electrodes before injecting the electrolyte, avoiding the misalignment of the electrode and the composite diaphragm during the battery production process, resulting in a short circuit that affects the battery safety performance, and improves the battery production yield; in a more preferred embodiment, taking the thickness of a single dry adhesive polymer coating as 100%, the thickness of a single wet adhesive polymer coating is 50-80%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80% or a range consisting of any two of them; this arrangement can To ensure that before the electrolyte is injected, the dry adhesive polymer is first in contact with and adheres to the positive and negative electrode sheets, thereby further improving the bonding strength between the polymer coated diaphragm and the positive and negative electrode sheets, further avoiding the misalignment of the electrode sheets and the diaphragm during the production process of the battery, resulting in a short circuit that affects the safety performance of the battery, thereby further improving the production yield of the battery; and the difference in thickness between the dry adhesive polymer coating and the wet adhesive polymer coating can also form a space between the wet adhesive polymer coating and the electrode sheet, which is conducive to the rapid infiltration of the polymer coating from the formed space after the electrolyte is injected, especially the infiltration of the wet adhesive polymer coating, so that the wet adhesive polymer after infiltration absorbs liquid more quickly and swells to contact the electrode sheet, quickly realizing the bonding of the polymer coating in a wet state, and further improving the bonding performance of the polymer coating.

[0032] In the present invention, there is no particular limitation on the specific thickness of a single first coating and a single second coating, and any thickness that meets the use requirements in the field can be applied to the present invention; based on the considerations of battery energy density and cycle capacity, it is preferred to limit the thickness of a single first coating and a single second coating to be independently 0.3 to 5 μm, for example, 0.3 μm, 0.5 μm, 0.9 μm, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm, 2.3 μm, 2.6 μm, 2.8 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm or a range consisting of any two of them.

[0033] In the utility model, there is no special restriction on the width of the blank area; in a preferred embodiment, the width of a single blank area is limited to 0.1-5 mm, for example, 0.1 mm, 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2 mm, 2.2 mm, 2.5 mm, 2.8 mm, 3 mm, 3.2 mm, 3.5 mm, 3.8 mm, 4 mm, 4.2 mm, 4.5 mm, 4.8 mm, 5 mm or a range consisting of any two of them.

[0034] In the present invention, there is no special requirement for the type of the base film, as long as its width meets the requirements, an existing porous membrane can be selected or a porous coated membrane can be prepared according to an existing method, illustratively, including any one of non-woven fabrics, polyolefin porous membranes or coated membranes.

[0035] Among them, the polyolefin porous membrane is any one of a polyethylene porous membrane, a polypropylene porous membrane or a polyethylene-polypropylene multilayer composite membrane; the "polyethylene-polypropylene multilayer composite membrane" refers to a multilayer composite porous membrane formed by stacking polypropylene (PP) and polyethylene (PE) in any order, for example, it can be a PP-PE-PP three-layer composite membrane, a PP-PE two-layer composite membrane or a PP-PP-PE-PP four-layer composite membrane, etc.

[0036] At the same time, there is no particular limitation on the coating layer of the porous coated diaphragm, and a coating layer commonly used in the art can be selected according to needs. For example, the material of the coating layer can be a mixed coating layer of at least one or more of inorganic ceramic particles (such as alumina, boehmite, silica, magnesium oxide, etc.), inorganic nanofibers, organic nanofibers, solid electrolyte particles (such as LATP, LAGP, etc.) or polymer resins (such as polyimide, PMMA, etc.); for example, the porous coated diaphragm can be any one of an alumina-coated polyolefin porous membrane, a boehmite-coated polyolefin porous membrane, a cellulose nanofiber-coated polyolefin porous membrane, a polyimide-coated polyolefin porous membrane, a PMMA-coated polyolefin porous membrane, a LATP-coated polyolefin porous membrane, a polyolefin porous membrane mixed with cellulose nanofibers and alumina, a polyolefin porous membrane mixed with LATP and cellulose nanofibers, or a porous membrane mixed with PMMA and alumina.

[0037] The utility model does not particularly limit the thickness and porosity of the base film. Based on the performance of lithium-ion secondary batteries, the thickness of the base film is preferably 0.5-25μm, for example, 0.5μm, 1μm, 2μm, 4μm, 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 25μm or a range consisting of any two of them. The porosity of the base film is preferably 25% to 60%, for example, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or a range consisting of any two of them.

[0038] In a second aspect, the utility model provides a lithium ion secondary battery, wherein the lithium ion secondary battery comprises the composite diaphragm as described in the first aspect.

[0039] Compared with the prior art, the utility model has the following beneficial effects:

[0040] The composite diaphragm provided by the utility model comprises a base film, at least one surface of the base film and part of its pores are provided with at least one first coating, at least one second coating and at least one blank area, the first coating and / or the second coating are wet-bonded polymer coatings, the first coating and the second coating are alternately distributed along the width direction of the base film, at least one of the blank areas is arranged between the first coating and the second coating, and the cross-sectional shapes of all the first coatings are regular trapezoids, and the cross-sectional shapes of all the second coatings are inverted trapezoids; by limiting at least one of the first coating and the second coating to be a wet-bonded polymer coating, and limiting the cross-sectional shapes and alternating distribution of the two, the first coating and the second coating can restrict each other in space, and can fit tightly along their respective oblique edges after pressure is applied, thereby greatly improving the wet bonding performance of the composite diaphragm with the positive and negative electrodes, and at the same time, there is no need to change the existing slurry formula, which is more suitable for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 A schematic diagram of the top view of the composite diaphragm provided in Example 1;

[0042] Figure 2 A schematic cross-sectional view of the composite diaphragm provided in Example 1;

[0043] Figure 3 A schematic diagram of the top view of the composite diaphragm provided in Example 2;

[0044] Figure 4 A schematic diagram of the top view of the composite diaphragm provided in Example 3;

[0045] Figure 5 A schematic cross-sectional view of the composite diaphragm provided in Example 5;

[0046] Figure 6 A schematic cross-sectional structure diagram of the composite diaphragm provided in Comparative Example 1;

[0047] Among them, 100-base film, 200-first coating, 300-second coating, 400-blank area, m-width of a single first coating, n-width of a single second coating, b-width of a single blank area, d-thickness of a single first coating, k-thickness of a single second coating, A-width direction of the base film. DETAILED DESCRIPTION

[0048] In the description of the present utility model, it should be noted that the orientation or position relationship indicated by the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside", etc. is based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present utility model and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present utility model; the terms "first", "second", and "third" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance. In addition, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present utility model can be understood according to specific circumstances.

[0049] The technical solution provided by the present invention will be clearly and completely described below in conjunction with the accompanying drawings and embodiments. Obviously, the specific implementation methods described are only part of the implementation methods of the present invention, rather than all the implementation methods.

[0050] Example 1

[0051] A composite diaphragm, the schematic diagram of which is viewed from above Figure 1 As shown, the cross-sectional structural diagram is as follows Figure 2 As shown, it includes a base film 100, the width of the base film is 305 mm, and 5 first coatings 200, 4 second coatings 300 and 8 blank areas 400 are respectively arranged on the two surfaces of the base film 100 and in some holes thereof;

[0052] Along the width direction of the base film 100 ( Figure 1 and Figure 2 In the direction indicated by the arrow A in the middle, five first coating layers 200 and four second coating layers 300 are arranged alternately, and a blank area 400 is arranged between two adjacent first coating layers 200 and second coating layers 300;

[0053] And along the length direction of the base film 100 (perpendicular to Figure 1 and Figure 2 In the direction indicated by the arrow A), each first coating 200 is distributed on the surface of the base film 100 in a three-dimensional network, and each second coating 300 is distributed on the surface of the base film 100 in a continuous three-dimensional network;

[0054] The thickness of the base film 100 is 20 μm, and it is specifically a polyethylene porous film (purchased from Shenzhen Xingyuan Material Technology Co., Ltd., model SW320H);

[0055] The first coating 200 is a polyvinylidene fluoride dry bonding coating, each of which has a thickness d of 2 μm and a cross-sectional shape of a regular trapezoid, with an upper side length (i.e., width m) of 25 mm and a lower side length of 35 mm;

[0056] The second coating 300 is a polyamide-imide wet bonding coating, and each second coating 300 has a thickness k of 1.5 μm, a cross-sectional shape of an inverted trapezoid, an upper side length (i.e., width n) of 35 mm, and a lower side length of 25 mm;

[0057] The width b of each blank area 400 is 5 mm.

[0058] Example 2

[0059] A composite diaphragm, the schematic diagram of which is viewed from above Figure 3 As shown, the difference between it and Example 1 is that:

[0060] The width of the base film is 375 mm. Four first coatings 200, four second coatings 300 and seven blank areas 400 are respectively arranged on the two surfaces of the base film 100 and in some holes thereof, and along the width direction of the base film 100 ( Figure 3 In the direction indicated by the arrow A in the middle), four first coating layers 200 and four second coating layers 300 are arranged alternately, and a blank area 400 is arranged between adjacent first coating layers 200 and second coating layers 300;

[0061] The other structures, parameters and preparation methods are the same as those in Example 1.

[0062] Example 3

[0063] A composite diaphragm, the schematic diagram of which is viewed from above Figure 4 As shown, the difference between it and Example 1 is that:

[0064] The width of the base film is 315 mm. Four first coatings 200, five second coatings 300 and eight blank areas 400 are respectively arranged on the two surfaces of the base film 100 and in some holes thereof, and the width direction of the base film 100 ( Figure 4 In the direction indicated by the arrow A in the middle, four first coating layers 200 and five second coating layers 300 are arranged alternately, and a blank area 400 is arranged between adjacent first coating layers 200 and second coating layers 300;

[0065] The other structures, parameters and preparation methods are the same as those in Example 1.

[0066] Example 4

[0067] A composite diaphragm, which differs from Example 1 in that the width of the base film is 265.8 mm, the width b of each blank area 400 is 0.1 mm, and other structures, parameters and preparation methods are the same as those of Example 1.

[0068] Example 5

[0069] A composite diaphragm, the cross-sectional structure diagram of which is as follows Figure 5 As shown, the difference between it and Example 1 is that:

[0070] The width of the base film is 230 mm, the cross-sectional shape of each first coating 200 is an inverted trapezoid, and the upper side length (i.e., width m) of the inverted trapezoid is 18 mm, and the lower side length is 15 mm, and the cross-sectional shape of each second coating 300 is a regular trapezoid, and the upper side length (i.e., width n) of the regular trapezoid is 25 mm, and the lower side length is 35 mm;

[0071] The other structures, parameters and preparation methods are the same as those in Example 1.

[0072] Example 6

[0073] A composite diaphragm is provided. The difference between the composite diaphragm and the embodiment 1 is that the thickness d of each first coating layer 200 is 2 μm, the thickness k of each second coating layer 300 is 2 μm, and the other structures, parameters and preparation methods are the same as those of the embodiment 1.

[0074] Example 7

[0075] A composite diaphragm is disclosed. The difference between the composite diaphragm and the embodiment 1 is that the first coating 200 is a polyacrylonitrile wet bonding coating. The other structures, parameters and preparation methods are the same as those of the embodiment 1.

[0076] Comparative Example 1

[0077] A composite diaphragm, the cross-sectional structure diagram of which is as follows Figure 6 As shown, the difference between it and Example 1 is that:

[0078] The width of the base film is 405 mm. Along the width direction of the base film 100, the cross-sectional shape of each first coating layer 200 is a rectangle, and the cross-sectional shape of each second coating layer 300 is a rectangle;

[0079] Other structures, parameters, materials and preparation methods are the same as those in Example 1.

[0080] Comparative Example 2

[0081] A composite diaphragm is provided. The difference between the composite diaphragm and the embodiment 1 is that the width of the base film is 265 mm, a blank area 400 is not provided between adjacent first coatings 200 and second coatings 300, and other structures, parameters and preparation methods are the same as those of the embodiment 1.

[0082] Comparative Example 3

[0083] A composite diaphragm, which differs from Example 7 in that the width of the base film is 265 mm, and along the width direction of the base film 100, the cross-sectional shape of each first coating 200 and the cross-sectional shape of each second coating 300 are both right trapezoids, and the upper side length (i.e., width m) of the right trapezoid is 25 mm, and the lower side length is 35 mm. Other structures, parameters and preparation methods are the same as those in Example 7.

[0084] Comparative Example 4

[0085] A composite diaphragm, which differs from Example 7 in that the width of the base film is 265 mm, no blank area 400 is provided between adjacent first coatings 200 and second coatings 300, and other structures, parameters and preparation methods are the same as those of Example 7.

[0086] Performance Test:

[0087] (1) Dry bonding strength: The diaphragm and electrode to be tested are cut into test strips with a size of 25 mm (width direction) × 60 mm (machine direction); the cut diaphragm sample strip is laminated with the electrode sample strip, and sandwiched between two cut gaskets (larger than the diaphragm size), and hot-pressed for 20 s at 100°C and 1.0 MPa, and then naturally cooled at room temperature. The hot-pressed diaphragm-electrode bonding strip is subjected to a 180° peel test using a tensile machine, with a test speed of 300 mm / min and a gauge length of 100 mm. After the test, the test result peel force F is recorded, and the value obtained by converting the peel force F to the width w (i.e., F / w) is used as the dry bonding strength (N / m) of the diaphragm and electrode to be tested;

[0088] (2) Wet adhesion: The test steps are as follows:

[0089] ① Stack a pole piece with a length × width of 70 mm × 15 mm and a diaphragm to be tested with a length × width of 90 mm × 20 mm, immerse them in electrolyte, soak them at 60°C for 24 hours, clamp them with two gaskets (larger than the diaphragm size) after they are fully soaked, hot press them at 85°C and 1.0 MPa for 30 minutes, and then cool them naturally at room temperature to obtain a laminated body formed by bonding the pole piece and the diaphragm;

[0090] ② A 3M tape with a width of 1 cm is pasted on the electrode side of the laminate (i.e., the tape is adhered to the surface of the electrode facing away from the diaphragm), and the other side of the 3M tape is pasted on a glass plate (3 mm thick, 150 mm long, and 50 mm wide) so that the diaphragm is parallel to the length direction of the glass plate, and it is used as a peeling test piece; ③ Using a universal testing machine, the peeling test piece is clamped into the chuck on the side of the load sensor, and a 90° peeling test is performed at a test speed of 50 mm / min; the measured values ​​of the stroke of 20 mm to 70 mm in the peeling test are averaged, and the averaged value is used as the peeling force of the peeling test piece, and the peeling force is measured from the peeling test piece, and the average value F of the peeling force is converted to the width w (i.e., F / w), which is used as the electrolyte infiltration wet bonding force (N / m) between the diaphragm and the electrode;

[0091] In the above tests (1) and (2), the electrode sheet includes a positive electrode sheet and a negative electrode sheet;

[0092] The preparation method of the positive electrode sheet includes: mixing lithium cobalt oxide, Super P and PVDF according to a mass ratio of 85wt%, 10wt% and 5wt%, and adding them to NMP to prepare a positive electrode slurry, and then coating the obtained positive electrode slurry on the front and back surfaces of an aluminum foil, and after drying and rolling, forming a positive electrode active material layer on the front and back surfaces of the aluminum foil to obtain the positive electrode sheet;

[0093] The preparation method of the negative electrode sheet comprises: mixing graphite, Super P and PVDF according to a mass ratio of 85wt%, 10wt% and 5wt%, and adding the mixture into deionized water to prepare a negative electrode slurry; then coating the obtained negative electrode slurry on the front and back surfaces of a copper foil, and after drying and rolling, forming a negative electrode active material layer on the front and back surfaces of the copper foil to obtain the negative electrode sheet;

[0094] The electrolyte is composed of EC:EMC:DM in a volume ratio of 3:2:5 and lithium hexafluorophosphate (LiPF6) with a mass percentage of 11%.

[0095] The composite diaphragms provided by Examples 1 to 7 and Comparative Examples 1 to 4 were tested according to the above test method. The test results are shown in Table 1:

[0096] Table 1

[0097]

[0098] Note: “ / ” in Table 1 means that the test was not performed because the dry binder polymer was not included.

[0099] From the data in Table 1, we can see that:

[0100] (1) The composite separators provided in Examples 1 to 7 have excellent wet bonding properties with both the positive and negative electrode sheets, with a wet bonding strength with the positive electrode sheet of up to 4.6 N / m and a wet bonding strength with the negative electrode sheet of up to 3.8 N / m;

[0101] (2) Compared with Example 1, the cross-sectional shapes of the first coating layer and the second coating layer in the composite separator provided in Comparative Example 1 are both rectangular, and there is no spatial restriction on each other, so that the wet bonding force between the obtained composite separator and the positive and negative electrode sheets is relatively low.

[0102] (3) Compared with Example 1, no blank area is set between the first coating layer and the second coating layer in the composite diaphragm provided in Comparative Example 2, which will affect the wetting effect of the coating layer after the electrolyte is injected, and thus also result in lower wet adhesion between the obtained composite diaphragm and the positive and negative electrode sheets.

[0103] (4) Compared with Example 7, the cross-sectional shapes of the first coating and the second coating in the composite diaphragm provided in Comparative Example 3 are both right trapezoids. Even if both are set as wet bonding polymer coatings, since the two have no mutual restriction effect, the wet bonding force between the obtained composite diaphragm and the positive and negative electrode sheets is relatively low.

[0104] (5) Compared with Example 7, no blank area is set between the first coating and the second coating in the composite diaphragm provided in Comparative Example 4. Even if both are set as wet-bonded polymer coatings, the absence of a blank area will affect the wetting effect of the coating after the electrolyte is injected, which also results in a lower wet bonding force between the obtained composite diaphragm and the positive and negative electrode sheets.

[0105] (6) Further comparison of the data of Examples 1 to 7 also reveals that the number, thickness and total width of the wet bonding polymer coating and the dry bonding polymer coating will also affect the wet bonding performance of the resulting composite separator and the positive and negative electrode sheets.

[0106] The applicant declares that the utility model illustrates a composite diaphragm and a lithium-ion secondary battery through the above-mentioned embodiments, but the utility model is not limited to the above-mentioned process steps, that is, it does not mean that the utility model must rely on the above-mentioned process steps to be implemented. The technicians in the relevant technical field should understand that any improvement to the utility model, the equivalent replacement of the raw materials selected by the utility model, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the utility model.

Claims

1. A composite diaphragm, characterized in that: The composite diaphragm comprises a base membrane, at least one surface of the base membrane and part of its pores are provided with at least one first coating layer, at least one second coating layer and at least one blank area; The first coating and / or the second coating is a wet-bonded polymer coating; Along the width direction of the base film, the first coating layer and the second coating layer are alternately distributed, at least one of the blank areas is arranged between the first coating layer and the second coating layer, and the cross-sectional shapes of all the first coating layers are regular trapezoids, and the cross-sectional shapes of all the second coating layers are inverted trapezoids; The width of the base film is 0.2 to 8 m.

2. The composite diaphragm according to claim 1, characterized in that: The first coating is a dry adhesive polymer coating, and the second coating is a wet adhesive polymer coating; Alternatively, the first coating is a wet adhesive polymer coating, and the second coating is a dry adhesive polymer coating.

3. The composite diaphragm according to claim 1, characterized in that: Along the length direction of the base film, each of the first coatings is continuously or discontinuously distributed on the surface of the base film and in some of its pores, and each of the second coatings is continuously or discontinuously distributed on the surface of the base film and in some of its pores.

4. The composite diaphragm according to claim 2, characterized in that: The number of the dry adhesive polymer coating layers is greater than the number of the wet adhesive polymer coating layers.

5. The composite diaphragm according to claim 2, characterized in that: The total width of the wet-state adhesive polymer coating is ≥ the total width of the dry-state adhesive polymer coating.

6. The composite diaphragm according to any one of claims 1 to 5, characterized in that: Based on the width of the base film being 100%, the width of the single wet-bonded polymer coating layer is 1 to 50%.

7. The composite diaphragm according to claim 2, characterized in that: The thickness of a single dry adhesive polymer coating layer is greater than the thickness of a single wet adhesive polymer coating layer.

8. The composite diaphragm according to claim 7, characterized in that: Taking the thickness of the single dry adhesive polymer coating as 100%, the thickness of the single wet adhesive polymer coating is 50-80%.

9. The composite diaphragm according to claim 1, characterized in that: The width of the blank area is 0.1-5 mm.

10. A lithium ion secondary battery, characterized in that: The lithium-ion secondary battery comprises the composite separator according to any one of claims 1 to 9.